Effect of simulation-based training method on the psychological health promotion in operating room students during the educational internship - Gholamreza Mohammadi; Maedeh Tourdeh; Abbasali Ebrahimian (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Simulation is one of the strategies which are suggested and used to reduce stress and anxiety in clinical student education. This study aimed to determine the effect of simulation-based training method on psychological health promotion in operating room students in their educational internships. MATERIALS AND METHODS: This study was a clinical trial. Research population was operating room students at Semnan University of Medical Sciences. A demographic questionnaire and the Spielberger's Situational Anxiety Inventory were used as data collection tools. Students were divided into two intervention and control groups randomly. Situational anxiety was measured before the intervention and on the 1st and the last days of the internship. The data from the two groups were compared by using the Mann-Whitney and Friedman statistics at the significant level of 0.05. RESULTS: There was a significant difference between students' situational anxiety scores in the experimental and control groups on the 1st day of internship after education by simulation (P = 0.481). There was a significant difference between the students' anxiety scores in the two groups on the last day of the internship (P = 0.008). CONCLUSION: Simulation of the operating room environment before the internship cannot reduce the operating room students' situational anxiety on the 1st day of internship, but it can reduce their situational anxiety during the internship and significantly reduce it at the end of internship compared to those who are not in the simulated environment.